PREVENTION OF THE PROGRESSION OF CHRONIC HEART FAILURE AFTER COVID-19 USING ANGIOTENSIN RECEPTOR NON-LYSINE INHIBITOR - Nasirova G. A. (Scholars Digest Publishing, 2024)
The review article is devoted to optimizing the treatment of chronic heart failure (CHF) in patients who have undergone COVID-19 using angiotensin receptor non-lysine inhibitors (ARNi). In the context of the COVID-19 pandemic, the cardiovascular system is one of the most frequently affected systems, and CHF can develop as a complication of infection. Arnis, which are a class of drugs combining the action of angiotensin receptor inhibitors and non-lysine inhibitors, have shown their effectiveness in improving the prognosis of CHF by reducing the load on the heart and improving heart function. The review of the articles highlights the importance of ARNi in the context of CHF treatment after COVID-19 and the need for further research to confirm their effectiveness and safety in this patient population.
Keywords: chronic heart failure, COVID-19, angiotensin receptor and non-lysine inhibitor, complex treatment.